2013
DOI: 10.1186/2008-2231-21-7
|View full text |Cite
|
Sign up to set email alerts
|

Metformin loaded non-ionic surfactant vesicles: optimization of formulation, effect of process variables and characterization

Abstract: BackgroundMetformin an oral hypoglycemic has been widely used as a fist line of treatment of Type II Diabetes but in a very high dose 2–3 times a day and moreover suffers from a number of side effects like lactic acidosis, gastric discomfort, chest pain, allergic reactions being some of them. The present work was conducted with the aim of sustaining the release of metformin so as to decrease its side effects and also reduce its dosing frequency using a novel delivery system niosomes (non-ionic surfactant vesic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 30 publications
1
37
0
Order By: Relevance
“…The lower volume of hydration medium may have led to incomplete or distorted formation of bilayer due to excess of material and low space. In order to accommodate the scarcity of water, the surface area of the produced vesicles was decreased and consequently the particle size increased (Sankhyan and Pawar, 2013).…”
Section: Effect Of Formulation Variables On Particle Size and Polydismentioning
confidence: 99%
“…The lower volume of hydration medium may have led to incomplete or distorted formation of bilayer due to excess of material and low space. In order to accommodate the scarcity of water, the surface area of the produced vesicles was decreased and consequently the particle size increased (Sankhyan and Pawar, 2013).…”
Section: Effect Of Formulation Variables On Particle Size and Polydismentioning
confidence: 99%
“…The equimolar CH-Span 1 60 mixture was selected since it proved to be very effective to give stable vesicles with good entrapment efficiency towards MTF (Sankhyan and Pawar, 2013). The presence of the charged surfactant enabled to obtain better results in terms of both smaller vesicle size (978.6 AE 51.9 nm), higher Zeta potential (À38.1 AE1.3 mV) and higher percent of entrapped drug (20.40%) compared to the simple CH-Span 1 60 mixture, that gives rise to vesicles of larger dimensions (1156.2 AE 86.1 nm) with lower Zeta potential (À26.0 AE 0.7 mV) and entrapment efficiency (16.46%) values.…”
Section: Niosomes Preparation and Characterizationmentioning
confidence: 99%
“…Niosomal formulations resulted suitable also for oral delivery of hypoglycemic agents (Pardakhty et al, 2007), including metformin (Sankhyan and Pawar, 2013), and demonstrated their effectiveness in prolonging drug release and improving its therapeutic effect (Hasan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies demonstrated that metformin is effective on metabolic differences between normal and abnormal metabolic pathways (Grzybowska et al, 2011;Pernicova & Korbonits, 2014;Sankhyan & Pawar, 2013). The reductions in the hepatic glucose output and plasma-fasting insulin level, and also the reduction in insulin resistance contribute significantly to the glucose-lowering action of metformin (Zhou et al, 2001;Viollet et al, 2012;McCulloch, 2015).…”
Section: Metformin and Type 2 Diabetesmentioning
confidence: 99%